Performance of Heat-Stressed Broilers Supplemented with Dietary Choline and Betaine - Kpodo, K.R.; Beckford, R.C.; Smith , M.O. (International Journal of Poultry Science, 2020)
Objective: A study was conducted to determine the effects of supplemental choline (CHO) and betaine (BET) on broiler performance and carcass characteristics under different temperature conditions, thermoneutral (TN: 23.9°C) and heat stress (HS: 28-36°C). Materials and Methods: The corn-soy bean basal (Control) diet was formulated to meet NRC requirements for broilers and supplemented with CHO and BET at 500 or 1000ppm (CHO500, CHO1000, BET500 and BET1000). Feed intake and body weight were recorded weekly by pen. On day 42, foot pads were assessed for health and litter samples collected from each pen. At slaughter on day 52, breast meat was collected for drip loss evaluation at 4 and 7 days post slaughter. Breast meat lightness (L*), redness (a*) and yellowness (b*) were measured. Results: Results showed that HS birds consumed 20.59% less feed and gained 23.34% less weight than TN birds (p